2023
DOI: 10.1681/asn.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

The Number and Size of Individual Kidney Medullary Pyramids is Associated with Clinical Characteristics, Kidney Biopsy Findings, and CKD Outcomes among Kidney Donors

Adriana V. Gregory,
Aleksandar Denic,
Amr Moustafa
et al.

Abstract: Background: The kidney is a lobulated organ, but little is known regarding the clinical importance of the number and size of individual kidney lobes. Methods: After applying a previously validated algorithm to segment cortex and medulla, a deep-learning algorithm was developed and validated to segment and count individual medullary pyramids on contrast-enhanced computed tomography (CT) images of living kidney donors prior to donation. The association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The clinical implications of kidney volume in relation to clinicodemographic factors that may be critical for health-related conditions remain largely unclear. Previous studies have shown a linkage between kidney volume and function [ 12 , 21 , 38 , 39 ] and a small kidney has been considered an indicator for increased risk of CKD or decreased renal function, as kidney volume is closely related to the number and size of nephrons, which determine kidney function [ 8 , 40–43 ]. Interestingly, kidney volume has previously been indicated to be associated with age, sex, weight and even muscle mass or intense physical activity [ 9 , 23–26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical implications of kidney volume in relation to clinicodemographic factors that may be critical for health-related conditions remain largely unclear. Previous studies have shown a linkage between kidney volume and function [ 12 , 21 , 38 , 39 ] and a small kidney has been considered an indicator for increased risk of CKD or decreased renal function, as kidney volume is closely related to the number and size of nephrons, which determine kidney function [ 8 , 40–43 ]. Interestingly, kidney volume has previously been indicated to be associated with age, sex, weight and even muscle mass or intense physical activity [ 9 , 23–26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Larger volumes are presumed to represent greater nephron endowment leading to increased glomerular filtration rate. 7,8 Correspondingly, patients with advanced CKD show significant shrinkage of the kidneys as a result of atrophy. 9 However, the causal directionality between TKV and CKD has not been tested beyond observational studies.…”
Section: Introductionmentioning
confidence: 99%